The effects of putrescine application against aluminum toxicity in wheat (Triticum Aestivum) roots - (:unkn) unknown (Nova Science Publishers, Inc., 2020)
Aluminum (Al) is the 3rd most found element in the earth’s crust. Complex Al transforms into a phytotoxic form in acidic soil by dissolving. Al+3 toxicity causes productivity and quality loss especially in the farm lands. The main goal of the present study is to reveal the alternative characteristics of 0.5 mM and 1 mM putrescine (Put) application together with 100 ΜM AlCl3 in wheat roots for 96 h. In the present study distilled water was used as control and 0.5 mM and 1 mM Put used as positive control. To alleviate the adverse effects of 100 ΜM AlCl3 0.5mM and 1mM Put were added to Al solution. According to our results, 100 ΜM AlCl3 application caused root growth inhibition, Al accumulation, deformation of plasma membrane, reduction in mitotic index, lipid peroxidation and increase in antioxidative enzyme activities. In alleviation groups, 0.5 mM Put alleviated the adverse effects of Al, however 1mM Put is observed being more effective than 0.5 mM. The survey not only suggested that Al toxicity has dangerous effects but also different concentrations of Put, as a polyamine has healing effects on plant growing. The results are intended to contribute to studies on the improvement of Al-induced toxicity, especially in agronomic plants. © 2020 Nova Science Publishers, Inc. All rights reserved.
Keywords: Aluminum toxicity; Antioxidant enzyme activity; Mitotic index; Putrescine; Root; Wheat